Christian Origins - Horsley, Richard A. (Book collections on Project MUSE., 2010)
Each stage of Christian church history is reinterpreted according to the laity, the common faithful, and everyday practices of faith at each stage. Normal histories focus on church doctrine or famous clergy of the period, while these works analyze each historical period in light of the common member's various interpretations of faith.